Auditor Industry Specialization and Real Earnings Management (Journal of Applied Business and Economics, 2023)
Empirical research examining auditors and real earnings management is limited and inconsistent. In this study, I focus on firms with the same auditor and view the change in audit quality as exogenous when the auditor gains other clients and becomes an industry leader. I examine the impact of firms’ earnings management associated with this change in audit quality. Consistent with the notion that industryspecialized auditors try to alleviate their discomfort associated with real earnings management, I find a significant decrease in the extent of real earnings management after a firm’s auditor becomes an industry specialist. In addition, this decrease is significantly larger than that for firms audited by non-specialized auditors.
Keywords: business; economics; real earnings management; audit quality; industry-specialized auditor; earnings quality; auditor change